Heat stress in vegetables: impacts and management strategies - a review - Oyebamiji, Yusuf Opeyemi; Noraziyah Abd Aziz Shamsudin,; Asmuni Mohd Ikmal,; Mohd Rafii Yusop, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Global climate change has not only caused a significant rise in the average temperature around the world but has also threatened crop productivity and food security. Heat stress disrupts various plant physiological and biochemical processes, such as inhibition of growth and development, reduction of photosynthesis rate and nutrient uptake, consequently causing yield losses. The destructive effects of heat stress are expected to worsen in the coming years. Thus, it has become imperative to understand how vegetables respond and adapt to heat stress in order to improve their heat tolerance ability. Various approaches have been adopted to enhance heat stress tolerance in vegetables, including modifying cultural practices and crop improvements through several breeding methods. This review gives comprehensive and up-to-date information on the effects of heat stress on vegetables; and existing as well as emerging methods adopted to enhance heat tolerance in vegetables. It also provides a brief overview of a new method called speed breeding, which can be leveraged to fast-track the breeding process for developing heat stress-tolerant vegetables.